Synthesis of (-)-phaitanthrin D and (+)-dihydropyrroloindoloquinazolinone - Vaidya, Sagar D.; N. P. Argade (Synthesis-Stuttgart, 2016)
The synthesis of (-)-phaitanthrin D and (+)-dihydropyrroloindoloquinazolinone are reported starting from the corresponding especially designed enantiomerically pure pivotal anthranilamide based building blocks using HMDS/ZnCl2 and NaHMDS.